Preoperative Molecular Markers in Thyroid Nodules - Sahli, Zeyad T.; Smith, Philip W.; Umbricht, Christopher B.; Zeiger, Martha A. (Frontiers in Endocrinology, 2018)
The need for distinguishing benign from malignant thyroid nodules has led to the pursuit of differentiating molecular markers. The most common molecular tests in clinical use are Afirma® Gene Expression Classifier (GEC) and Thyroseq® V2. Despite the rapidly developing field of molecular markers, several limitations exist. These challenges include the recent introduction of the histopathological diagnosis ‘Non-Invasive Follicular Thyroid neoplasm with Papillary-like nuclear features’ (NIFTP), the correlation of genetic mutations within both benign and malignant pathologic diagnoses, the lack of follow-up of molecular marker negative nodules, and the cost-effectiveness of molecular markers. In this manuscript, we review the current published literature surrounding the diagnostic value of Afirma® GEC and Thyroseq® V2. Among Afirma® GEC studies, sensitivity (Se), specificity (Sp), positive predictive value (PPV), and negative predictive value (NPV) ranged from 75% – 100%, 5 – 53%, 13 – 100%, and 20 – 100%, respectively. Among Thyroseq® V2 studies, Se, Sp, PPV, and NPV ranged from 40% – 100%, 56% – 93%, 13% – 90%, and 48% – 97%, respectively. We also discuss current challenges to Afirma® GEC and Thyroseq® V2 utility and clinical application, and preview the future directions of these rapidly developing technologies.